STORY FILM AS A MEDIA IN LEARNING NARRATIVE WRITING AT THIRD SEMESTER STUDENTS IN ENGLISH DEPARTMENT FACULTY OF TEACHER TRAINING AND EDUCATION - Andi Asry Jumiaty (UIN Alauddin Makassar, 2016)
The objectives of this research is to find out wheter or not the use of story films as the media can improve the students’ narrative writing at third semester in English Department Faculty of Teacher Training and Education Muhammadiyah University of Makassar. This research used class action research that consisted two cycles with four steps namely: planning, acting, observing and reflection. Cycle 1 observes the students competence in writing narrative using film as media. After finding the results of the cycle 1, the researcher continued cycle 2 to improve the result of the students’ in narrative writing. Populations was the third semester English Department Faculty of Teacher Training and Education Muhammadiyah University of Makassar academic year 2015/2016, the sample of this research consisted of 30 students. The result shows that the students’ writing achievement in term of content in descriptive text, pre-test was 55 and post-test was 76.68. the improvement of the students’ writing achievement in term of content is 39.41%. the significant increase of the students’ writing achievement in term of content is proved by t-test is higher than t-table, 8.468> 2.331. It means that the Null Hypothesis (HO) is rejected and the Alternative Hypothesis (HI) is accepted, where the t-test is greater than t-table. The students’ writing achievement in term of organization in descriptive text, pre-test was (56.18), and post-test was (79). The improvement of the students’ writing achievement in term of organization is 40.61%. The significant increase of the students’ writing achievement in term of organization is proved by t-test is higher than t-table, 9.272> 2.331. It means that the Null Hypothesis (HO) is rejected and the Alternative Hypothesis (HI) is accepted, where the t-test is greater than t-table.